Load Frequency Robust Control Considering Intermittent Characteristics of Demand-Side Resources - Guoxin Ming; Jian Geng; Jiantao Liu; Yiyuan Chen; Kun Yuan; Kaifeng Zhang (Energies, 2022)
Renewable energy has the characteristics of low carbon and environmental protection compared to traditional water and thermal power, but it also has the intermittency and uncertainty that traditional water and thermal power does not have. These characteristics make the inertia of the power system increase, which greatly affects the frequency stability of the grid. To solve such problems, the participation of demand-side resources (DSRs) in the dispatch of power systems has become a viable solution.However, unlike generation-side resources, DSRs have their own unique characteristics. In this paper, by taking into account a load frequency control system (LFC) with intermittent demand-side resources, the robust H∞ load frequency control problem are discussed in detail.A robust controller to coordinate the load side with the resource side is introduced. A critical stability criterion and robust performance evaluation of the new LFC system was carried out. Finally, simulation results based on the new LFC system are provided to demonstrate that the proposed control strategy can effectively improve the stability and robustness of the grid under large disturbances, thus allowing the grid frequency to return to the reference value.